Dividend Policy, Profitability, and Capital Structure: Their Effects on the Value of Family and Non-Family Firms in Indonesia - Wina Febriyandini; Wirawan Suhaedi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study was to determine the differences in the influence of dividend policy, profitability, and capital structure on the value of family and non-family companies. The population in this study is made up of manufacturing companies listed on the IDX in 2018–2022. The population in this study amounted to 166 companies. The sample was obtained using the purposive sampling technique, which resulted in 154 companies with 770 observation data. Furthermore, testing was carried out with multiple linear regression tests and different tests using paired sample t tests. The results of this study indicate that there is no significant difference between the effect of dividend policy and capital structure on the value of family and non-family companies. It was found that jointly, dividend policy, profitability, and capital structure can affect the firm value of both family and non-family firms.